A study of the impact of blast induced conditioning on leaching performance. (April 2015) - Parra, Hector; Onederra, Italo; Michaux, Simon; Kuhar, Laura; McFarlane, Angus; Chapman, Nicole
Highlights: A leachable synthetic material was developed for controlled blasting experiments. The impact of blast conditioning on recovery was studied. Experiments showed that conditioning does not always improve recovery. Abstract: Recent investigations have alluded to possible improvements of ore extraction efficiency by leaching due to blast induced fragment conditioning. This paper presents results from a series of controlled blasting tests supported by blast modelling and statistical analysis to study the effect of conditioning on copper extraction in laboratory leaching tests. A leachable synthetic material was developed and selected from 19 different preparations. It was possible to control copper grade distributions and provide homogeneous and isotropic characteristics to this material. Combined statistical analysis of four individual controlled blasting tests exhibited no statistical difference in copper extraction between unblasted material and material subjected to a low degree of conditioning. In contrast, the percent copper extraction increased by 0.84% in the intermediate conditioning zones, which translates to an overall improvement in copper extraction efficiency of 39.7%. Leaching tests proved that increasing the blast conditioning does not necessarily improve percent copper extraction. The majority of fractures were generated along grains boundaries and not across the matrix. Therefore, conditioning may not be able to expose a significant amount of copper particles consistently to significantly impact extraction efficiency. In practical terms, the contribution of blast induced conditioning to leaching performance is in the increased probability of exposing mineral species to leaching paths.